Analisis Tingkat Kesehatan Bank dengan Metode RGEC Pada BCA Syariah dan Panin Dubai Syariah - andriani andriani; Indah Permatasari (IQTISHODUNA, 2021)
This research is motivated by the development of increasingly rapid Islamic banking and increasing public trust in banks. Bank health services are one of the management controls because bank health is a reflection of the bank's performance. This study aims to see, describe and compare the soundness level of banks at BCA Syariah and Panin Dubai Syariah using the RGEC method (Risk Profile, GCG, Earning, Capital) with new SEOJK Number 10 / SEOJK.03 / 2014. The results show that the NPF BCA Syariah and Panin Dubai Syariah are in a very healthy position. FDR BCA Syariah is in a fairly healthy position and Panin Dubai Syariah is in an unhealthy position. ROA BCA Syariah and Panin Dubai Syariah are in a fairly healthy position. NOM BCA Syariah and Panin Dubai Syariah are in a healthy position. CAR BCA Syariah and Panin Dubai Syariah are in a very healthy position. The BCA Syariah GCG Report is in a very healthy position and the Panin Dubai Syariah GCG Report is in a healthy position. The analysis results show a significant difference between the performance of BCA Syariah and Panin Dubai Syariah, especially in the NPF, FDR, NOM and CAR variables, while there is no difference in the ROA variable.